Epidendrum falsigarayi - Hágsater, Eric (2019)
Similar to Epidendrum garayi Løjtnant but the flower brick-red, petals and margin of lip wine-red (vs. greenish purple), sepals 12.0-12.3 x 6.0-6.3 mm, ovate (vs. sepals 10-12 x 3.0-4.0 mm, oblong-lanceolate, lateral sepals falcate), petals 8.6 x 4.4 mm, triangular-ovate, acute (vs. petals 10.5- 11.5 x 2.5-3.0 mm, lanceolate, shortly acuminate, falcate), and lip widely cordiform (vs. lip cordiform). Epiphytic, sympodial, branching, pendulous herb, to ca. 40 cm long, with successive sub-apical growths, forming long chains of short stems, sometimes branching from a middle internode. Roots 1 mm in diameter, terete, thin, white, generally produced from the basal stems only. Stems to 50 x 2.5 mm, simple, cane-like, terete, thin, pendent, formed by 3-5 internodes, short, secund, facing the same direction, the internodes covered by infundibuliform, acute, non-foliar sheaths to 12 mm long. Leaves 3-4[-6], aggregate at the apex of the apical internode, sub-pendent, coriaceous, articulate, similar in size and shape; sheaths 2-3 mm long, tubular, minutely striated when dry; blade to 25-50 x 3-5 mm, linearlanceolate, acuminate, margin serrulate towards the apex, spreading. Spathe lacking. Inflorescence apical, sessile, 1-flowered, flowering only once.